Entrepreneurial Orientation and Corruption - Karmann, Tobias (Journal of business ethics, 2016)
Organizational corruption is a wide-spread negative aspect of economic activity, and a seemingly never-ending series of corruption scandals has been made public around the globe. Although research is performed in a broad variety of disciplines, ranging from psychology to management to law, a fully satisfactory explanation for the causes of organizational corruption has not been found. By looking at organizational factors as potential triggers for corruptive behavior, this study draws upon the concept of entrepreneurial orientation (EO). Diverse studies have shown that EO, as an antecedent to company performance, has a positive effect. Recent EO literature, however, indicates that EO has not only positive but also negative consequences. In this line of reasoning, this study builds upon principal agent theory and makes a first step in exploring the impact of EO on a negative aspect of business behavior, namely organizational corruption. We gathered survey data and publicly available data from 411 firms, inquiring for both acts of corruption from within the top management team over the last 3 years and the level of entrepreneurial orientation within the organization. Results show diverging effects along the individual dimensions of EO; they point to risk orientation as the dark side of EO, as it significantly increases the likelihood of corrupt behavior in companies. In contrast, innovation orientation, to a certain extent, counterbalances by reducing the likelihood of corrupt behavior.